Reflections and Their Real Space Significance - Arnold, Emily (Cranfield University, 2020)
Bone is a complex composite material made up of three main components, the most abundant of which is the mineral hydroxyapatite. Within many species, hydroxyapatite naturally occurs as a nanocrystalline material, making accurate analysis difficult. Brilliant X-ray sources are used to allow measurement of a much wider range of angular data (from Q = 0.05 to 60 Å-1) than a traditional laboratory X-ray diffractometer (from Q = 0.1 to 8 Å-1). Shown here is diffraction data collected at Diamond Light Source on the dedicated total scattering beamline I15-1. Debye-Scherrer rings can be seen, allowing measurement of crystallographic parameters within reciprocal space. Shadows are seen from the sample changer and an additional detector. This beamline allows for the observation of local coordination of atoms from 0.1nm to 5 nm (through pair distribution function analysis) while simultaneously measuring average crystallite structure.
Keywords: 'DSDS20 Digital Image'; 'DSDS20'; 'X-ray Diffraction'; 'Bone'; 'Hydroxyapatite'; 'Biomechanics'